2010
DOI: 10.1002/maco.200905620
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion performance of epoxy coatings modified by nanoparticulate SiO2

Abstract: Electrochemical impedance spectroscopy (EIS) was employed to investigate the corrosion performance of nanoparticulate SiO 2 modified epoxy coatings on carbon steel in 3.5 wt% NaCl solution, coupled with salt spray test. Capacitancegravimetric methods and delamination tests were performed to analyze the water uptake behavior and interface stability against delamination of modified coatings, respectively. Four systems were studied, including a clear coating and three pigmented coatings (with 1, 2, and 3 wt% nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 25 publications
(16 reference statements)
2
15
0
Order By: Relevance
“…At the same time, composites reinforced with differently sized particles displayed different results in terms of compactness, dispersibility, and barrier, which significantly influenced their anticorrosion behaviors under water conditions. Li et al [16] investigated the anti-corrosion behaviors of nano SiO 2 -modified EP coatings, and Mostafaei et al [17] investigated the anti-corrosion behaviors of ZnO nanoparticle-modified polyaniline coatings. The results showed that nano composite coatings can act as either a physical barrier toward a corrosive environment, or as inhibitory pigments by shifting the corrosion potential of the metallic substrate to higher values and reducing the corrosion rate.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, composites reinforced with differently sized particles displayed different results in terms of compactness, dispersibility, and barrier, which significantly influenced their anticorrosion behaviors under water conditions. Li et al [16] investigated the anti-corrosion behaviors of nano SiO 2 -modified EP coatings, and Mostafaei et al [17] investigated the anti-corrosion behaviors of ZnO nanoparticle-modified polyaniline coatings. The results showed that nano composite coatings can act as either a physical barrier toward a corrosive environment, or as inhibitory pigments by shifting the corrosion potential of the metallic substrate to higher values and reducing the corrosion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Al is evaporated by the conventional flash method. SiO x preparation and sublimation are described elsewhere [6].…”
Section: Methodsmentioning
confidence: 99%
“…The flexural strength of self-compacting concrete can be improved by adding up to 4 wt% SiO 2 nanoparticles; however, the strength is reduced when the addition is over this amount [288]. The anticorrosion performance of epoxy-coated mild steel can be improved by the addition of 2 wt% SiO 2 nanoparticles; however, when the addition is over this amount, the number of pores in the coating is increased, thus having a negative impact on corrosion inhibition [223].…”
Section: Functional Fillermentioning
confidence: 98%